Preparation method of anti-overcharge thermal runaway negative electrode material, battery and application thereof

By preparing the negative electrode graphite material with a loaded Pt/Fe2O3 catalyst, the problem of thermal runaway in the overcharge state of lithium iron phosphate batteries is solved, and higher safety and performance are achieved.

CN119706823APending Publication Date: 2025-03-28BATTEROTECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411838790.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing lithium iron phosphate batteries are prone to thermal runaway under overcharge, resulting in safety hazards and reduced performance.

Method used

The negative electrode graphite material supported by Pt/Fe2O3 catalyst is prepared by using emulsified asphalt, ammonium ferric citrate and sodium chloride, through mechanical stirring, heating and stirring, freeze-drying and solid-phase sintering to prevent overcharge and heat loss.

Benefits of technology

It effectively extends the time when CO concentration reaches its peak, prevents thermal runaway, reduces the battery's heat production in thermal runaway, and improves the safety and performance of lithium iron phosphate batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706823A_ABST
    Figure CN119706823A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an overcharge thermal runaway prevention negative electrode material, a battery and application thereof, and relates to the technical field of battery preparation, and the preparation method comprises the following steps: mechanically stirring emulsified asphalt in distilled water to obtain a first solution; adding ammonochloroplatinum, ammonium ferric citrate and sodium chloride into the first solution according to a preset mass ratio to obtain a second solution; heating the second solution and stirring to obtain a third solution; freeze-drying the third solution to obtain a first solid composition; heating the first solid composition to a first preset temperature and keeping the temperature to obtain a second solid composition; cooling the second solid composition to room temperature and grinding; heating the ground second solid composition in the heating cavity to a second preset temperature, and keeping the temperature to obtain a third solid composition; and washing the third solid composition with distilled water, and drying to obtain the overcharge thermal runaway prevention negative electrode material. The preparation method can be used for preparing the negative electrode material which is low in cost, non-toxic and efficient and is capable of preventing overcharge thermal runaway.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery preparation, and in particular to a method for preparing a negative electrode material that prevents overcharging and thermal runaway, a battery, and applications thereof. Background Art

[0002] In the current technical field, various measures have been taken to improve the performance of lithium iron phosphate batteries in response to the overcharge problem. One common method is to add special additives to the electrolyte, such as shuttling agents and flame retardants.

[0003] The shuttle agent is stable under normal charging voltage and will not react. However, once the battery is overcharged, these shuttle agents will undergo a redox reaction at a specific voltage. This reaction can consume excess electrical energy in a reversible way, thereby effectively protecting the battery from overcharge damage. The introduction of flame retardant additives further improves the safety of the electrolyte in overcharge conditions and prevents possible fire or explosion accidents.

[0004] However, these additives may decompose during overcharging, resulting in the formation of polymer or passivated solid electrolyte interphase (SEI) films on the electrode surface. The formation of these substances will increase the internal resistance of the battery, thereby reducing the charge and discharge performance of the battery. Summary of the invention

[0005] The present application provides a method for preparing an overcharge and thermal runaway-proof negative electrode material, a battery and applications thereof, which can prepare a low-cost, non-toxic and efficient overcharge and thermal runaway-proof negative electrode material.

[0006] In a first aspect, the present application provides a method for preparing an overcharge-proof thermal runaway negative electrode material, the preparation method comprising:

[0007] Step S100: mechanically stirring the emulsified asphalt in distilled water according to a preset solid-liquid ratio to obtain a first solution;

[0008] In the above step S100, emulsified asphalt is added to distilled water according to a preset solid-liquid ratio, and is fully mixed by mechanical stirring to obtain a first solution. Using asphalt as a raw material can not only achieve effective recycling of waste, but also significantly reduce the cost of the production process.

[0009] Step S200: adding ammonia chloroplatinum, ammonium ferric citrate and sodium chloride in a preset mass ratio into the first solution to obtain a second solution;

[0010] In the above step S200, by adding a preset mass ratio of ammonia chloroplatinum, ammonium ferric citrate and sodium chloride into the first solution, the desired intermediate product second solution can be obtained. In this way, specific chemical substances can be introduced into the solution to lay the foundation for subsequent chemical reactions.

[0011] Step S300: heating the second solution and stirring it, so that the solutes in the second solution react with each other to obtain a third solution;

[0012] In this process, the heating temperature and stirring speed are precisely controlled to ensure that the chemical reaction is fully carried out. Through this step, chemical substances such as ammonia chloroplatinum, ammonium ferric citrate, sodium chloride and emulsified asphalt can be reacted to form a specific complex or precipitate. The specific complex or precipitate contained in this third solution provides the necessary chemical basis for the subsequent steps.

[0013] Step S400: freeze-drying the third solution to obtain a first solid composition;

[0014] Freeze-drying technology can effectively remove the solvent portion of the solution while retaining the structure and properties of the solute portion.

[0015] Step S500: heating the first solid composition to a first preset temperature in a heating chamber and keeping the temperature constant to obtain a second solid composition;

[0016] In the heating chamber, by precisely controlling the heating temperature and the holding time, the first solid composition can undergo further chemical changes, thereby obtaining a second solid composition with better performance. Compared with the first solid composition, the second solid composition has improved structure and properties.

[0017] Step S600: cooling the second solid composition to room temperature and grinding;

[0018] By cooling the second solid composition to room temperature, changes in the properties of the material due to excessively high temperatures during the grinding process can be avoided. The grinding process can break the solid composition into finer particles, which not only helps to improve the reactivity of the material, but also increases its uniformity in subsequent applications.

[0019] Step S700: heating the ground second solid composition to a second preset temperature in a heating chamber and keeping the temperature to obtain a third solid composition;

[0020] The performance of the material can be further improved by secondary heating treatment. This treatment method is suitable for occasions such as the present application where the stability and uniformity of the material need to be improved. The third solid composition is obtained based on the further heating treatment of the second solid composition after grinding, so its performance and uniformity are significantly improved compared to the second solid composition.

[0021] Step S800: washing the third solid composition with distilled water, and drying to obtain an overcharge thermal runaway prevention negative electrode material;

[0022] In the above steps, by using distilled water to carefully wash the third solid composition, it can be ensured that all potential impurities and unwanted chemicals are completely removed, thereby ensuring the purity and performance of the negative electrode material.

[0023] Among them, the protective gas is filled in the heating chamber, and the negative electrode material to prevent overcharging and thermal runaway is a negative electrode graphite material with a loaded Pt / Fe2O3 catalyst.

[0024] Filling the heating chamber with protective gas can prevent the material from being oxidized at high temperatures. The final anti-overcharge thermal runaway negative electrode material is a negative electrode graphite material with a loaded Pt / Fe2O3 catalyst, which can effectively prevent the battery from thermal runaway under overcharge conditions, thereby improving the safety performance of the battery.

[0025] This application improves the negative electrode material in a low-cost and green way while using asphalt to turn waste into treasure, and prepares a Pt / Fe2O3-loaded catalyst composite negative electrode material, that is, solid-phase sintering-mechanical grinding-solid-phase sintering is used to finally prepare a battery that prevents overcharge thermal runaway. In the thermal runaway test, the lithium iron phosphate battery with Pt / Fe2O3-loaded catalyst prolonged the time for CO concentration to reach the peak, effectively preventing the occurrence of thermal runaway, while avoiding the large-scale generation of other toxic gases. Temperature detection proves that this method can effectively reduce the heat generation of the battery in thermal runaway, avoid the destruction of the material crystals due to overcharging of the battery, and help improve the safety of lithium iron phosphate batteries.

[0026] In some examples, based on the above step S100, the preset solid-liquid ratio of the emulsified asphalt is 1 g / mL:20 g / mL, and the emulsified asphalt is mechanically stirred in distilled water for 0.25 h-1 h to obtain a first solution.

[0027] According to the above step S100, the preset solid-liquid ratio of the emulsified asphalt involved is set to 1 gram per milliliter to 20 grams per milliliter, that is, 1g / mL:20g / mL. At this ratio, the emulsified asphalt is placed in distilled water and treated by mechanical stirring. The stirring process lasts for a period of time ranging from 0.25 hours to 1 hour. Through such treatment, the desired first solution of emulsified asphalt can be successfully prepared.

[0028] In some examples, based on the above step S200, in the step of adding ammonia chloroplatinum, ammonium ferric citrate and sodium chloride in a preset mass ratio into the first solution to obtain the second solution:

[0029] The preset mass ratio of ammonia chloroplatin, ammonium ferric citrate, sodium chloride and emulsified asphalt is: 1:5:5:89;

[0030] Alternatively, the preset mass ratio of ammonia chloroplatin, ammonium ferric citrate, sodium chloride and emulsified asphalt is: 1:3:7:89.

[0031] According to the above step S200, a process of adding ammonia chloroplatinum, ammonium ferric citrate and sodium chloride in a specific mass ratio to a first solution is involved to prepare a second solution. In this process, firstly, a first solution needs to be prepared, and then ammonia chloroplatinum, ammonium ferric citrate and sodium chloride are added thereto according to a predetermined ratio. Through such steps, a second solution containing these components can be obtained.

[0032] In some examples, based on the above step S300, the step of heating the second solution and stirring, and the solutes in the second solution reacting with each other to obtain the third solution includes:

[0033] heating the second solution to 40°C-100°C;

[0034] The heated second solution is stirred for 2 h to 10 h to obtain a third solution.

[0035] In the above steps, in order to obtain the third solution, the second solution needs to be heated and stirred. The specific operation includes heating the second solution to a temperature range of 40°C to 100°C, and then stirring the solution for 2 hours to 10 hours while heating. Through such treatment, it can be ensured that the solute in the solution is fully reacted, thereby obtaining the desired third solution.

[0036] In some examples, the second solution is heated to 45° C. and stirred for 10 hours during the heating process, and then freeze-dried for 12 hours to obtain a first solid composition;

[0037] Alternatively, the second solution is heated to 50° C. and stirred for 12 hours during the heating process, and then freeze-dried for 12 hours to obtain a first solid composition;

[0038] Alternatively, the second solution was heated to 80° C. and stirred for 10 h during heating, and then freeze-dried for 12 h to obtain the first solid composition.

[0039] The second solution can be heated to 45° C. and stirred for 10 hours during the heating process, and then freeze-dried for 12 hours to obtain a first solid composition.

[0040] The second solution can also be heated to a temperature of 50° C. and stirred for 12 hours during the heating process, and then freeze-dried for 12 hours to obtain the first solid composition;

[0041] The second solution can also be heated to 80° C. and stirred for 10 hours during the heating process, and then freeze-dried for 12 hours to obtain the first solid composition.

[0042] In some examples, based on the above step S500, the step of heating the first solid composition to a first preset temperature in the heating chamber and keeping the temperature to obtain the second solid composition includes:

[0043] Filling the heating chamber with protective gas;

[0044] placing a first solid composition in a heating chamber;

[0045] Raise the temperature to 400°C-550°C at a heating rate of 5°C-15°C;

[0046] The temperature is maintained for 10 h to 24 h to obtain a second solid composition.

[0047] According to the above step S500, the step of heating the first solid composition to a first preset temperature in the heating chamber and keeping the temperature to obtain the second solid composition can be described in detail as follows:

[0048] First, a protective gas is filled in the heating chamber to ensure that the first solid composition does not react unnecessarily with oxygen in the air during the heating process, thereby protecting the chemical properties of the material;

[0049] Then, the first solid composition is placed in the heating chamber, ensuring that it is properly positioned so as to be evenly heated;

[0050] Next, the temperature is gradually increased at a heating rate of 5°C-15°C until it reaches a temperature range of 400°C-550°C, which is carefully selected based on the thermal stability of the material and the characteristics of the desired reaction;

[0051] Finally, after reaching the target temperature, the temperature is maintained for 10 to 24 hours, which is long enough to ensure that the chemical reaction in the first solid composition can be fully carried out, thereby obtaining a uniform and stable second solid composition.

[0052] The heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 550° C. at a heating rate of 5° C., and the temperature is kept for 12 hours to obtain the second solid composition;

[0053] Alternatively, the heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 450° C. at a heating rate of 10° C., and the temperature is maintained for 12 hours to obtain the second solid composition;

[0054] Alternatively, the heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 550° C. at a heating rate of 10° C., and the temperature is maintained for 24 hours to obtain the second solid composition.

[0055] The above exemplifies three implementation methods for forming the second solid composition. Nitrogen is used as the protective gas in all three implementation methods. Other suitable protective gases may also be used as needed.

[0056] In the first embodiment, first, a nitrogen filling operation is performed in the heating chamber to ensure that the chamber is filled with nitrogen to exclude oxygen and prevent the occurrence of oxidation reaction. Subsequently, the second solid composition is placed in the heating chamber filled with nitrogen. Next, the heating program is started, and the temperature is gradually increased to 550°C at a heating rate of 5°C per minute. After reaching the target temperature, the temperature is maintained unchanged and the heat preservation treatment is carried out for 12 hours. Through such a heating and heat preservation process, a heat-treated second solid composition can be obtained.

[0057] In the second embodiment, first, nitrogen is also filled in the heating chamber to ensure that the internal environment of the chamber is an inert gas atmosphere. Then, the second solid composition is placed in the heating chamber. The heating device is started, and the temperature is gradually increased to 450°C at a heating rate of 10°C per minute. When the temperature reaches 450°C, the heating is stopped, the temperature is kept constant, and the heat preservation treatment is performed, and the heat preservation time is also 12 hours. Through this heating and heat preservation step, the desired second solid composition can be prepared.

[0058] In the third embodiment, after the heating chamber is filled with nitrogen, the second solid composition is placed in the chamber. The heating program is started, and the temperature is gradually increased to 550° C. at a heating rate of 10° C. per minute. After reaching 550° C., the temperature is continued to be kept, but the temperature keeping time is extended to 24 hours. Through this long-term temperature keeping treatment, a second solid composition that has been fully heat-treated can be obtained.

[0059] The above three implementations are only exemplary embodiments, and do not mean that the preparation of the second solid composition in this application can only adopt the above implementations. The above parameters such as protective gas, addition rate, final insulation temperature, insulation time, etc. can be set as needed.

[0060] In some examples, based on the above step S700, the step of heating the ground second solid composition to a second preset temperature in a heating chamber and keeping the temperature to obtain a third solid composition includes:

[0061] Filling the heating chamber with protective gas;

[0062] In the above step, the heating chamber may be filled with a protective gas to ensure that the second solid composition does not react with oxygen in the air or other gases that may affect its properties during the heating process;

[0063] placing a second solid composition in the heating chamber;

[0064] The above steps can evenly place the ground second solid composition in the heating chamber to ensure that it is evenly heated during the heating process, thereby ensuring that the final third solid composition has uniform properties;

[0065] Raise the temperature to 550°C-800°C at a heating rate of 5°C-15°C;

[0066] The above step can be gradually heated at a heating rate of 5°C to 15°C per hour until a second preset temperature range of 550°C to 800°C is reached, and this temperature range is carefully selected based on the specific chemical properties of the second solid composition and the desired characteristics of the third solid composition;

[0067] The temperature is maintained for 5 h to 24 h to obtain a third solid composition.

[0068] In the above steps, after reaching the second preset temperature, the temperature can be maintained for 5 to 24 hours. The long-term heat preservation allows the various components in the second solid composition to fully react and transform, thereby obtaining a third solid composition with expected properties.

[0069] In some examples, the heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 750° C. at a heating rate of 5° C., and the temperature is maintained for 12 hours to obtain a third solid composition;

[0070] Alternatively, the heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 650° C. at a heating rate of 10° C., and the temperature is maintained for 12 hours to obtain a third solid composition;

[0071] Alternatively, the heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 800° C. at a heating rate of 10° C., and the temperature is maintained for 24 hours to obtain a third solid composition.

[0072] The above exemplifies three implementation methods for forming the third solid composition. Nitrogen is used as the protective gas in all three implementation methods. Other suitable protective gases may also be used as needed.

[0073] In the first embodiment, a heating chamber is filled with nitrogen, and then the second solid composition is placed in the heating chamber filled with nitrogen. Then, the temperature is gradually increased to 750 degrees Celsius at a heating rate of 5 degrees Celsius per minute, and kept constant at this temperature for 12 hours. Through such a treatment process, the desired third solid composition is finally obtained;

[0074] In the second embodiment, the heating chamber is also filled with nitrogen, and the second solid composition is placed in the heating chamber filled with nitrogen. The difference is that this time, they gradually increase the temperature to 650 degrees Celsius at a heating rate of 10 degrees Celsius per minute and keep the temperature constant for 12 hours. Through such a treatment process, the desired third solid composition is finally obtained;

[0075] In the third embodiment, the heating chamber is also filled with nitrogen, and the second solid composition is placed in the heating chamber filled with nitrogen. The temperature is gradually increased to 800 degrees Celsius at a heating rate of 10 degrees Celsius per minute, and kept constant at this temperature for 24 hours. Through such a treatment process, the desired third solid composition is finally obtained.

[0076] The above three implementations are only exemplary embodiments, and do not mean that the preparation of the third solid composition in this application can only adopt the above implementations. The above parameters such as protective gas, addition rate, final insulation temperature, insulation time, etc. can be set as needed.

[0077] In a second aspect, the present application provides a battery, wherein the negative electrode material in the battery is made using the method for preparing the negative electrode material for preventing overcharge thermal runaway as described above.

[0078] The negative electrode material made by the above-mentioned method for preparing the negative electrode material to prevent overcharge and thermal runaway can reduce costs and improve the safety of the battery. Specifically, the present application improves the negative electrode material in a low-cost and green way and uses asphalt to turn waste into treasure, and prepares a Pt / Fe2O3-loaded catalyst composite negative electrode material, that is, solid phase sintering-mechanical grinding-solid phase sintering is adopted to finally prepare a battery to prevent overcharge and thermal runaway. The lithium iron phosphate battery with Pt / Fe2O3-loaded catalyst prolonged the time for the CO concentration to reach the peak in the thermal runaway test, effectively preventing the occurrence of thermal runaway, while avoiding the large-scale generation of other toxic gases. Temperature detection proves that this method can effectively reduce the heat generation of the battery in thermal runaway, avoid the damage of the material crystals caused by overcharging of the battery, and help to improve the safety of the lithium iron phosphate battery.

[0079] In a second aspect, the present application provides an electrical device, which uses the above-mentioned battery. The electrical device includes a device body, and the battery is installed in the device body.

[0080] After the battery with the above-mentioned anti-overcharge thermal runaway negative electrode material is applied to electrical equipment, it can reduce costs and improve the safety of the equipment. Specifically, the present application improves the negative electrode material in a low-cost and green way and uses asphalt to turn waste into treasure, and prepares a Pt / Fe2O3 supported catalyst composite negative electrode material, that is, solid phase sintering-mechanical grinding-solid phase sintering is adopted to finally prepare a battery that prevents overcharge thermal runaway. In the thermal runaway test, the lithium iron phosphate battery with Pt / Fe2O3 supported catalyst prolonged the time for the CO concentration to reach the peak, effectively preventing the occurrence of thermal runaway, and avoiding the large-scale generation of other toxic gases. Temperature detection proves that this method can effectively reduce the heat generation of the battery in thermal runaway, avoid the damage of the material crystals caused by overcharging of the battery, and help to improve the safety of the lithium iron phosphate battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] In order to more clearly illustrate the technical solutions in the present application or the prior art, the drawings required for use in the examples or prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some examples of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0082] Figure 1 Schematic diagram of the process of preparing a negative electrode material for preventing overcharge thermal runaway in an example of the present application.

[0083] Figure 2 This is a schematic diagram of the process for preparing the third solution in an example of the present application.

[0084] Figure 3 This is a schematic diagram of the process for preparing the second solid composition in one example of the present application.

[0085] Figure 4 This is a schematic diagram of the process for preparing the third solid composition in an example of the present application.

[0086] Figure 5 A schematic diagram of overcharge test data of a battery corresponding to an embodiment of the present application.

[0087] Figure 6 Schematic diagram of overcharge test data of a battery corresponding to the second embodiment of the present application.

[0088] Figure 7 Schematic diagram of overcharge test data of three corresponding batteries in the embodiments of the present application.

[0089] Figure 8 This is a schematic diagram of overcharge test data of a corresponding battery in a comparative example of the present application. DETAILED DESCRIPTION

[0090] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific examples described here are only used to explain the present application and are not used to limit the present application.

[0091] To solve the above technical problems, please refer to Figure 1-Figure 8 As shown, the first aspect of the present application proposes a method for preparing an anti-overcharge thermal runaway negative electrode material, which can prepare a low-cost, non-toxic and efficient anti-overcharge thermal runaway negative electrode material.

[0092] Reference Figure 1 In some examples, the present application provides a method for preparing an overcharge-proof thermal runaway negative electrode material, the preparation method comprising:

[0093] Step S100: mechanically stirring the emulsified asphalt in distilled water according to a preset solid-liquid ratio to obtain a first solution;

[0094] In the above step S100, emulsified asphalt is added to distilled water according to a preset solid-liquid ratio, and is fully mixed by mechanical stirring to obtain a first solution. Using asphalt as a raw material can not only achieve effective recycling of waste, but also significantly reduce the cost of the production process. Emulsified asphalt is a stable dispersion system formed by mixing asphalt and water, which is commonly used in road construction and waterproofing materials. The asphalt of the present application can be made by collecting waste. A solution is a uniform mixture of two or more substances, one of which is a solvent and the other is a solute.

[0095] Step S200: adding ammonia chloroplatinum, ammonium ferric citrate and sodium chloride in a preset mass ratio into the first solution to obtain a second solution;

[0096] In the above step S200, by adding a preset mass ratio of ammonia chloroplatinum, ammonium ferric citrate and sodium chloride into the first solution, the desired intermediate product second solution can be obtained. In this way, specific chemical substances can be introduced into the solution to lay the foundation for subsequent chemical reactions.

[0097] Through the above process, ammonia chloroplatinum can provide the required platinum element, ammonium ferric citrate is responsible for providing the iron element, and sodium chloride can promote the dissolution or reaction of ammonia chloroplatinum and ammonium ferric citrate, or help form a specific complex or precipitation. This series of addition steps is fully prepared for the preparation of supported Pt / Fe2O3 catalysts. In the first solution, the presence of emulsified asphalt can provide the necessary carbon element, which makes it possible to directly produce graphite materials with supported Pt / Fe2O3 catalysts in the end. After further treatment and processing, this graphite material can eventually obtain a special negative electrode material, which has excellent performance in preventing overcharge thermal runaway, thereby providing higher safety and reliability in battery applications.

[0098] Step S300: heating the second solution and stirring it, so that the solutes in the second solution react with each other to obtain a third solution;

[0099] In this process, the heating temperature and stirring speed are precisely controlled to ensure that the chemical reaction is fully carried out. Through this step, chemical substances such as ammonia chloroplatinum, ammonium ferric citrate, sodium chloride and emulsified asphalt can be reacted to form a specific complex or precipitate. The specific complex or precipitate contained in this third solution provides the necessary chemical basis for the subsequent steps.

[0100] Step S400: freeze-drying the third solution to obtain a first solid composition;

[0101] The freeze-drying technology can effectively remove the solvent part of the solution while retaining the structure and properties of the solute part. This drying method is suitable for the occasion of the present application where the original structure and properties of the substance need to be maintained. Therefore, through this step, the specific complex or precipitate in the third solution can be separated to form the first solid composition.

[0102] Step S500: heating the first solid composition to a first preset temperature in a heating chamber and keeping the temperature constant to obtain a second solid composition;

[0103] In the heating chamber, by precisely controlling the heating temperature and the holding time, the first solid composition can undergo further chemical changes, thereby obtaining a second solid composition with better performance. Compared with the first solid composition, the second solid composition has improved structure and properties.

[0104] Step S600: cooling the second solid composition to room temperature and grinding;

[0105] By cooling the second solid composition to room temperature, changes in the properties of the material due to excessively high temperatures during the grinding process can be avoided. The grinding process can break the solid composition into finer particles, which not only helps to improve the reactivity of the material, but also increases its uniformity in subsequent applications.

[0106] Step S700: heating the ground second solid composition to a second preset temperature in a heating chamber and keeping the temperature to obtain a third solid composition;

[0107] The performance of the material can be further improved by secondary heating treatment. This treatment method is suitable for occasions such as the present application where the stability and uniformity of the material need to be improved. The third solid composition is obtained based on the further heating treatment of the second solid composition after grinding, so its performance and uniformity are significantly improved compared to the second solid composition.

[0108] Step S800: washing the third solid composition with distilled water, and drying to obtain an overcharge thermal runaway prevention negative electrode material;

[0109] In the above steps, by using distilled water to carefully wash the third solid composition, it can be ensured that all potential impurities and unwanted chemicals are completely removed, thereby ensuring the purity and performance of the negative electrode material. After washing, the third solid composition is dried to ensure that the material does not contain any excess moisture, which is essential for maintaining the stability of the material and extending its service life. Through this series of treatments, the final negative electrode material will have the ability to prevent thermal runaway caused by overcharging, which is of great significance for improving the safety and reliability of the battery.

[0110] Among them, the protective gas is filled in the heating chamber, and the negative electrode material to prevent overcharging and thermal runaway is a negative electrode graphite material with a loaded Pt / Fe2O3 catalyst. The negative electrode graphite material with a loaded Pt / Fe2O3 catalyst can be expressed as C@Pt / Fe2O3. A catalyst is a substance that can accelerate the rate of a chemical reaction, but does not undergo permanent changes after the reaction.

[0111] Filling the heating chamber with protective gas can prevent the material from being oxidized at high temperatures. The final anti-overcharge thermal runaway negative electrode material is a negative electrode graphite material with a loaded Pt / Fe2O3 catalyst, which can effectively prevent the battery from thermal runaway under overcharge conditions, thereby improving the safety performance of the battery.

[0112] Compared with existing technologies, traditional methods for preparing negative electrode materials are often accompanied by high costs and serious environmental pollution problems. The preparation method proposed in this application, by using asphalt as a raw material, not only realizes the recycling of waste, but also significantly reduces production costs. In addition, compared with traditional wet chemical methods, the solid-phase sintering and mechanical grinding techniques adopted in this application simplify the process flow and reduce pollution to the environment. More importantly, the composite negative electrode material prepared in this application shows better performance in the battery overcharge test, effectively prolongs the time for CO concentration to reach its peak, and significantly reduces the heat generation of the battery in a thermal runaway state, thereby greatly improving the safety of the battery. Through these technical improvements and innovations, this application not only overcomes the shortcomings of the prior art, but also achieves performance improvement and optimization of production quality.

[0113] This application improves the negative electrode material in a low-cost and green way while using asphalt to turn waste into treasure, and prepares a Pt / Fe2O3-loaded catalyst composite negative electrode material, that is, solid-phase sintering-mechanical grinding-solid-phase sintering is used to finally prepare a battery that prevents overcharge thermal runaway. In the thermal runaway test, the lithium iron phosphate battery with Pt / Fe2O3-loaded catalyst prolonged the time for CO concentration to reach the peak, effectively preventing the occurrence of thermal runaway, while avoiding the large-scale generation of other toxic gases. Temperature detection proves that this method can effectively reduce the heat generation of the battery in thermal runaway, avoid the destruction of the material crystals due to overcharging of the battery, and help improve the safety of lithium iron phosphate batteries.

[0114] The chemical formula of the above-mentioned ammonia chloroplatinum is Pt(NH3)2Cl2, which is a chemical substance containing platinum and ammonia. Platinum is a precious metal, ammonia is a compound of nitrogen and hydrogen, and chloride is a salt containing chlorine. In this process, Pt(NH3)2Cl2 is used as a source of platinum to provide platinum atoms. Ammonium ferric citrate is an organic metal compound containing iron and citrate, as well as ammonium ions. It may be used as an iron source in this process to provide iron elements for the preparation of materials. Emulsified asphalt is a viscous liquid composed of hydrocarbons, which is commonly used in road construction and waterproofing materials. In this process, emulsified asphalt may be used as a dispersant or carrier material. Freeze drying is a technique that removes water from a solution or suspension by freezing and then sublimating it under low pressure, and is often used to retain the structure and chemical properties of the substance. Solid-phase sintering is a process that bonds solid particles together by heating, and can also be used to prepare ceramic and metal materials. Here, it is used to fuse different components in the material together. Mechanical grinding is a physical method that crushes solid materials into smaller particles by grinding to increase the surface area and reactivity of the material. Graphite is an allotrope of carbon with good electrical conductivity and high temperature resistance. In battery materials, graphite is often used as a negative electrode material. The negative electrode material of the present application is a low-cost, non-toxic and efficient negative electrode graphite material with a supported Pt / Fe2O3 catalyst.

[0115] Ammonia platinum (diammine dichloroplatinum) Pt(NH3)2Cl2, the application of this ammonia platinum chemical in batteries is mainly reflected in its role as a catalyst. In fuel cells, ammonia platinum can be used as part of the electrode material to help improve the efficiency of electrochemical reactions, especially in oxygen reduction reactions. Due to its excellent catalytic performance, ammonia platinum can reduce the overpotential of the battery and improve the energy conversion efficiency of the battery, thereby extending the service life of the battery. In addition, ammonia platinum may also be used as an additive in batteries to improve the battery's charge and discharge performance and cycle stability.

[0116] In some examples, based on the above step S100, the preset solid-liquid ratio of the emulsified asphalt is 1 g / mL:20 g / mL, and the emulsified asphalt is mechanically stirred in distilled water for 0.25 h-1 h to obtain a first solution.

[0117] According to the above step S100, the preset solid-liquid ratio of the emulsified asphalt involved is set to 1 gram per milliliter to 20 grams per milliliter, that is, 1g / mL:20g / mL. At this ratio, the emulsified asphalt is placed in distilled water and treated by mechanical stirring. The stirring process lasts for a period of time ranging from 0.25 hours to 1 hour. Through such treatment, the desired first solution of emulsified asphalt can be successfully prepared.

[0118] The above-mentioned first solution involves a method for preparing emulsified asphalt. Emulsified asphalt is a stable system formed by dispersing asphalt in water. The above-mentioned preset solid-liquid ratio is an exemplary ratio, specifically taking 1 gram of solid asphalt corresponding to 20 grams and milliliters of distilled water as an example, which means that during the emulsification process, 20 grams and milliliters of water are required for every 1 gram of asphalt. It can also be adjusted to other solid-liquid ratios as needed, such as 1g / mL:15g / mL, 1g / mL:18g / mL, 1g / mL:25g / mL, 1g / mL:30g / mL, etc.

[0119] The asphalt and distilled water can be mixed by mechanical stirring for a period of 0.25 hours to 1 hour, so that a more uniform emulsified asphalt solution, namely the first solution mentioned above, can be obtained. The specific stirring time can also be 0.5 hours, 0.8 hours, etc., or a longer stirring time, such as 1.5 hours, etc., can be used according to actual needs.

[0120] Solid-to-liquid ratio refers to the mass or volume ratio of solid to liquid in a mixture. Distilled water is water that has been distilled to remove impurities. It is pure water that does not contain minerals and other impurities. Mechanical mixing refers to the use of mechanical equipment (such as a stirrer) to mix two or more substances to achieve a uniform mixture. The mixing time refers to the length of time that mechanical mixing is continued during the preparation of emulsified asphalt. In this case, the mixing time needs to be controlled between 0.25 hours and 1 hour to ensure the emulsification effect.

[0121] In some examples, based on the above step S200, in the step of adding ammonia chloroplatinum, ammonium ferric citrate and sodium chloride in a preset mass ratio into the first solution to obtain the second solution:

[0122] The preset mass ratio of ammonia chloroplatin, ammonium ferric citrate, sodium chloride and emulsified asphalt is: 1:5:5:89;

[0123] Alternatively, the preset mass ratio of ammonia chloroplatin, ammonium ferric citrate, sodium chloride and emulsified asphalt is: 1:3:7:89.

[0124] According to the above step S200, a process of adding ammonia chloroplatinum, ammonium ferric citrate and sodium chloride in a specific mass ratio to a first solution is involved to prepare a second solution. In this process, firstly, a first solution needs to be prepared, and then ammonia chloroplatinum, ammonium ferric citrate and sodium chloride are added thereto according to a predetermined ratio. Through such steps, a second solution containing these components can be obtained.

[0125] In these embodiments, the mass ratio of ammonia chloroplatinum, ammonium ferric citrate, sodium chloride and emulsified asphalt can be 1:5:5:89. This means that when preparing the second solution, 5 units of ammonium ferric citrate and 5 units of sodium chloride are required for every 1 unit of ammonia chloroplatinum, as well as 89 units of emulsified asphalt.

[0126] The mass ratio of ammonia chloroplatinum, ammonium ferric citrate, sodium chloride and emulsified asphalt can also be 1:3:7:89. According to this ratio, every 1 unit mass of ammonia chloroplatinum will be mixed with 3 units mass of ammonium ferric citrate, 7 units mass of sodium chloride and 89 units mass of emulsified asphalt to prepare the required second solution.

[0127] The above are only two exemplary embodiments, and the mass ratio of ammonia chloroplatinum, ammonium ferric citrate, sodium chloride and emulsified asphalt can also be 1:4:5:90, 1:5:6:88, 1:3:6:90, 1:6:6:87, etc., which can be selected according to actual needs. This ratio is important for the properties and uses of the final solution and may affect the performance of the material or the results of the chemical reaction.

[0128] Reference Figure 2 In some examples, based on the above step S300, the step of heating the second solution and stirring, and the solutes in the second solution reacting with each other to obtain the third solution includes:

[0129] Step S310: heating the second solution to 40° C.-100° C.;

[0130] Step S320: Stir the heated second solution for 2 h to 10 h to obtain a third solution.

[0131] In the above steps, in order to obtain the third solution, the second solution needs to be heated and stirred. The specific operation includes heating the second solution to a temperature range of 40°C to 100°C, and then stirring the solution for 2 hours to 10 hours while heating. Through such treatment, it can be ensured that the solute in the solution is fully reacted, thereby obtaining the desired third solution.

[0132] In chemical experiments, heating is a common operation used to increase the temperature of a solution to promote or accelerate chemical reactions. Stirring is a physical method that allows the substances in a solution to mix evenly, which helps the reactants to fully contact and promotes chemical reactions. The second solution is the solution produced in the previous step, which contains a specific solute. The third solution is the second solution after heating and stirring, in which the solute has reacted to form a new solution state, called the third solution. In this example, the solutes in the second solution interact with each other, resulting in the formation of the third solution.

[0133] The third solution is freeze-dried for 10-24 hours during the process of forming the first solid composition.

[0134] In the process of the third solution participating in forming the first solid composition, a freeze drying step is required, and the duration of this step is set to be between 10 and 24 hours. Through freeze drying technology, the solvent part in the solution can be effectively removed while retaining the structure and properties of the solute part.

[0135] In some examples, the second solution is heated to 45° C. and stirred for 10 hours during the heating process, and then freeze-dried for 12 hours to obtain a first solid composition;

[0136] Alternatively, the second solution is heated to 50° C. and stirred for 12 hours during the heating process, and then freeze-dried for 12 hours to obtain a first solid composition;

[0137] Alternatively, the second solution was heated to 80° C. and stirred for 10 h during heating, and then freeze-dried for 12 h to obtain the first solid composition.

[0138] The second solution can be heated to 45° C. and stirred for 10 hours during the heating process, and then freeze-dried for 12 hours to obtain a first solid composition.

[0139] The second solution can also be heated to a temperature of 50° C. and stirred for 12 hours during the heating process, and then freeze-dried for 12 hours to obtain the first solid composition;

[0140] The second solution can also be heated to 80° C. and stirred for 10 hours during the heating process, and then freeze-dried for 12 hours to obtain the first solid composition.

[0141] Reference Figure 3 In some examples, based on the above step S500, the step of heating the first solid composition to a first preset temperature in the heating chamber and keeping the temperature constant to obtain the second solid composition includes:

[0142] Step S510: filling the heating chamber with protective gas;

[0143] Step S520: placing the first solid composition in the heating chamber;

[0144] Step S530: heating to 400°C-550°C at a heating rate of 5°C-15°C;

[0145] Step S540: keeping warm for 10 h to 24 h to obtain a second solid composition.

[0146] In some specific embodiments, according to the above step S500, the step of heating the first solid composition to a first preset temperature in the heating chamber and keeping the temperature to obtain the second solid composition can be described in detail as follows:

[0147] First, a protective gas is filled in the heating chamber to ensure that the first solid composition does not react unnecessarily with oxygen in the air during the heating process, thereby protecting the chemical properties of the material;

[0148] Then, the first solid composition is placed in the heating chamber, ensuring that it is properly positioned so as to be evenly heated;

[0149] Next, the temperature is gradually increased at a heating rate of 5°C-15°C until it reaches a temperature range of 400°C-550°C, which is carefully selected based on the thermal stability of the material and the characteristics of the desired reaction;

[0150] Finally, after reaching the target temperature, the temperature is maintained for 10 to 24 hours, which is long enough to ensure that the chemical reaction in the first solid composition can be fully carried out, thereby obtaining a uniform and stable second solid composition.

[0151] The heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 550° C. at a heating rate of 5° C., and the temperature is kept for 12 hours to obtain the second solid composition;

[0152] Alternatively, the heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 450° C. at a heating rate of 10° C., and the temperature is maintained for 12 hours to obtain the second solid composition;

[0153] Alternatively, the heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 550° C. at a heating rate of 10° C., and the temperature is maintained for 24 hours to obtain the second solid composition.

[0154] The above exemplifies three implementation methods for forming the second solid composition. Nitrogen is used as the protective gas in all three implementation methods. Other suitable protective gases may also be used as needed.

[0155] In the first embodiment, first, a nitrogen filling operation is performed in the heating chamber to ensure that the chamber is filled with nitrogen to exclude oxygen and prevent the occurrence of oxidation reaction. Subsequently, the second solid composition is placed in the heating chamber filled with nitrogen. Next, the heating program is started, and the temperature is gradually increased to 550°C at a heating rate of 5°C per minute. After reaching the target temperature, the temperature is maintained unchanged and the heat preservation treatment is carried out for 12 hours. Through such a heating and heat preservation process, a heat-treated second solid composition can be obtained.

[0156] In the second embodiment, first, nitrogen is also filled in the heating chamber to ensure that the internal environment of the chamber is an inert gas atmosphere. Then, the second solid composition is placed in the heating chamber. The heating device is started, and the temperature is gradually increased to 450°C at a heating rate of 10°C per minute. When the temperature reaches 450°C, the heating is stopped, the temperature is kept constant, and the heat preservation treatment is performed, and the heat preservation time is also 12 hours. Through this heating and heat preservation step, the desired second solid composition can be prepared.

[0157] In the third embodiment, after the heating chamber is filled with nitrogen, the second solid composition is placed in the chamber. The heating program is started, and the temperature is gradually increased to 550° C. at a heating rate of 10° C. per minute. After reaching 550° C., the temperature is continued to be kept, but the temperature keeping time is extended to 24 hours. Through this long-term temperature keeping treatment, a second solid composition that has been fully heat-treated can be obtained.

[0158] The above three implementations are only exemplary embodiments, and do not mean that the preparation of the second solid composition in this application can only adopt the above implementations. The above parameters such as protective gas, addition rate, final insulation temperature, insulation time, etc. can be set as needed.

[0159] The step of cooling the second solid composition to room temperature and grinding comprises:

[0160] placing the second solid composition in a ball mill;

[0161] The above steps can place the second solid composition in the grinding chamber of the ball mill to ensure that the composition is evenly distributed among the grinding media so that the subsequent grinding process can be carried out efficiently.

[0162] Then, the ball mill is started to allow the grinding media to rotate or vibrate at a high speed in the ball mill. In this way, the second solid composition is gradually refined under the impact and friction of the grinding media.

[0163] The second solid composition was ground by a ball mill for 0.5 h to 4 h.

[0164] During the grinding process, the grinding time needs to be continuously monitored to ensure that the second solid composition is fully ground. According to an embodiment of the present invention, the grinding time should be controlled between 0.5 hours and 4 hours to ensure that the second solid composition reaches the desired particle size distribution.

[0165] Reference Figure 4 In some examples, based on the above step S700, the step of heating the ground second solid composition to a second preset temperature in a heating chamber and keeping the temperature constant to obtain a third solid composition includes:

[0166] Step S710: filling the heating chamber with protective gas;

[0167] In the above step, the heating chamber may be filled with a protective gas to ensure that the second solid composition does not react with oxygen in the air or other gases that may affect its properties during the heating process;

[0168] Step S720: placing the second solid composition in the heating chamber;

[0169] The above steps can evenly place the ground second solid composition in the heating chamber to ensure that it is evenly heated during the heating process, thereby ensuring that the final third solid composition has uniform properties;

[0170] Step S730: heating to 550°C-800°C at a heating rate of 5°C-15°C;

[0171] The above step can be gradually heated at a heating rate of 5°C to 15°C per hour until a second preset temperature range of 550°C to 800°C is reached, and this temperature range is carefully selected based on the specific chemical properties of the second solid composition and the desired characteristics of the third solid composition;

[0172] Step S740: Keep warm for 5 h to 24 h to obtain a third solid composition.

[0173] In the above steps, after reaching the second preset temperature, the temperature can be maintained for 5 to 24 hours. The long-term heat preservation allows the various components in the second solid composition to fully react and transform, thereby obtaining a third solid composition with expected properties.

[0174] In some examples, the heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 750° C. at a heating rate of 5° C., and the temperature is maintained for 12 hours to obtain a third solid composition;

[0175] Alternatively, the heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 650° C. at a heating rate of 10° C., and the temperature is maintained for 12 hours to obtain a third solid composition;

[0176] Alternatively, the heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 800° C. at a heating rate of 10° C., and the temperature is maintained for 24 hours to obtain a third solid composition.

[0177] The above exemplifies three implementation methods for forming the third solid composition. Nitrogen is used as the protective gas in all three implementation methods. Other suitable protective gases may also be used as needed.

[0178] In the first embodiment, a heating chamber is filled with nitrogen, and then the second solid composition is placed in the heating chamber filled with nitrogen. Then, the temperature is gradually increased to 750 degrees Celsius at a heating rate of 5 degrees Celsius per minute, and kept constant at this temperature for 12 hours. Through such a treatment process, the desired third solid composition is finally obtained;

[0179] In the second embodiment, the heating chamber is also filled with nitrogen, and the second solid composition is placed in the heating chamber filled with nitrogen. The difference is that this time, they gradually increase the temperature to 650 degrees Celsius at a heating rate of 10 degrees Celsius per minute and keep the temperature constant for 12 hours. Through such a treatment process, the desired third solid composition is finally obtained;

[0180] In the third embodiment, the heating chamber is also filled with nitrogen, and the second solid composition is placed in the heating chamber filled with nitrogen. The temperature is gradually increased to 800 degrees Celsius at a heating rate of 10 degrees Celsius per minute, and kept constant at this temperature for 24 hours. Through such a treatment process, the desired third solid composition is finally obtained.

[0181] The above three implementations are only exemplary embodiments, and do not mean that the preparation of the third solid composition in this application can only adopt the above implementations. The above parameters such as protective gas, addition rate, final insulation temperature, insulation time, etc. can be set as needed.

[0182] In the present application, the protective gas mentioned is an inert gas, which can be at least one of nitrogen, helium, neon, argon, krypton, xenon, and radon. Inert gases are widely used as protective gases in many industrial processes because of their stable chemical properties and are not easy to react chemically with other substances to prevent reactants from reacting unnecessarily with oxygen or other active gases in the air.

[0183] In applications of high temperature reactions, the protective gas can be specifically selected as nitrogen, or other inert gases including nitrogen, such as helium, neon, argon, krypton, xenon, radon, etc. These gases can provide a stable reaction environment under high temperature conditions to prevent the reactants from being oxidized or reacting with other active substances in the air.

[0184] Specifically, these gases can effectively prevent reactants from reacting with oxygen or other active gases in the air, thereby ensuring that the reaction is carried out in an oxygen-free or low-oxygen environment, improving the stability of the reaction and the purity of the product. Using inert gas as a protective gas can reduce the occurrence of side reactions, improve the selectivity of the reaction, and also help control the reaction temperature because inert gases generally have good thermal stability. In addition, the use of inert gas can also protect the reaction equipment from oxidation or corrosion, extending the service life of the equipment.

[0185] Combining all the above steps, this application shows three relatively independent embodiments and a comparative example, which are:

[0186] Embodiment 1:

[0187] In this embodiment, emulsified asphalt was first added to distilled water at a solid-liquid ratio of 1 g / mL:20 g / mL, and then treated by mechanical stirring for 0.5 hours, thereby successfully preparing a first solution.

[0188] Next, Pt(NH3)2Cl2, ammonium ferric citrate, sodium chloride and emulsified asphalt were added to the first solution prepared previously in a mass ratio of 1:5:5:89 to obtain a second solution.

[0189] The second solution was heated to 45° C. and stirred at this temperature for 10 hours to obtain a third solution;

[0190] The third solution was then freeze-dried for 12 hours to ensure that the water in the third solution was completely removed to obtain a first solid composition.

[0191] The dried first solid composition was then gradually heated to 550° C. at a heating rate of 5° C. per minute in a nitrogen-protected environment and kept at this temperature for 12 hours to complete the heat treatment process of the first solid composition to obtain a second fixed composition.

[0192] After the heat-treated second fixing composition was cooled to room temperature, it was ground using a ball mill for 2 hours to obtain finer particles.

[0193] After the grinding was completed, the material was heated to 750° C. at the same heating rate under nitrogen protection and kept at this temperature for 12 hours to further improve the properties of the material, so as to obtain a third solid composition.

[0194] The third solid composition after high temperature treatment is washed with distilled water to remove possible impurities, and then dried to obtain the final negative electrode graphite material C@Pt / Fe2O3.

[0195] Finally, the obtained negative electrode graphite material C@Pt / Fe2O3 was used to prepare soft-pack batteries to verify the electrochemical properties of the material.

[0196] Embodiment 2:

[0197] In this embodiment, emulsified asphalt was first added to distilled water at a solid-liquid ratio of 1 g / mL:20 g / mL, and then treated by mechanical stirring for 0.5 hours, thereby successfully preparing a first solution.

[0198] Next, Pt(NH3)2Cl2, ammonium ferric citrate, sodium chloride and emulsified asphalt were added to the first solution prepared previously in a mass ratio of 1:3:7:89 to obtain a second solution.

[0199] The second solution was heated to 50° C. and stirred at this temperature for 10 hours to obtain a third solution;

[0200] The third solution was then freeze-dried for 12 hours to ensure that the water in the third solution was completely removed to obtain a first solid composition.

[0201] The dried first solid composition is then gradually heated to 450°C at a heating rate of 10°C per minute in a nitrogen-protected environment and kept at this temperature for 12 hours to complete the heat treatment process of the first solid composition to obtain a second fixed composition.

[0202] After the heat-treated second fixing composition was cooled to room temperature, it was ground using a ball mill for 4 hours to obtain finer particles.

[0203] After the grinding was completed, the material was heated to 650° C. at the same heating rate under nitrogen protection and kept at this temperature for 12 hours to further improve the properties of the material, so as to obtain a third solid composition.

[0204] The third solid composition after high temperature treatment is washed with distilled water to remove possible impurities, and then dried to obtain the final negative electrode graphite material C@Pt / Fe2O3.

[0205] Finally, the obtained negative electrode graphite material C@Pt / Fe2O3 was used to prepare soft-pack batteries to verify the electrochemical properties of the material.

[0206] Embodiment three:

[0207] In this embodiment, emulsified asphalt was first added to distilled water at a solid-liquid ratio of 1 g / mL:20 g / mL, and then treated by mechanical stirring for 0.5 hours, thereby successfully preparing a first solution.

[0208] Next, Pt(NH3)2Cl2, ammonium ferric citrate, sodium chloride and emulsified asphalt were added to the first solution prepared previously in a mass ratio of 1:5:5:89 to obtain a second solution.

[0209] The second solution was heated to 80° C. and stirred at this temperature for 10 hours to obtain a third solution;

[0210] The third solution is then freeze-dried for 24 hours to ensure that the water in the third solution is completely removed to obtain a first solid composition.

[0211] The dried first solid composition is then gradually heated to 550°C at a heating rate of 10°C per minute in a nitrogen-protected environment and kept at this temperature for 24 hours to complete the heat treatment process of the first solid composition to obtain a second fixed composition.

[0212] After the heat-treated second fixing composition was cooled to room temperature, it was ground using a ball mill for 4 hours to obtain finer particles.

[0213] After grinding, the material was heated to 800° C. at the same heating rate under nitrogen protection and kept at this temperature for 24 hours to further improve the performance of the material, so as to obtain a third solid composition.

[0214] The third solid composition after high temperature treatment is washed with distilled water to remove possible impurities, and then dried to obtain the final negative electrode graphite material C@Pt / Fe2O3.

[0215] Finally, the obtained negative electrode graphite material C@Pt / Fe2O3 was used to prepare soft-pack batteries to verify the electrochemical properties of the material.

[0216] Comparative Example 1:

[0217] First, the emulsified asphalt was added into distilled water at a solid-liquid ratio of 1 g / mL:20 g / mL, and then stirred by mechanical stirring for 0.5 hours to form a uniform solution 1.

[0218] Next, add sodium chloride to the previously prepared solution 1 in a mass ratio of 5:89 between sodium chloride and emulsified asphalt, ensuring uniform mixing.

[0219] Then, the mixed solution was heated to 50°C and stirred at this temperature for 5 hours, and then freeze-dried for 24 hours.

[0220] The freeze-dried material was transferred to a nitrogen-protected environment, heated to 550°C at a heating rate of 5°C per hour, and kept at this temperature for 12 hours to complete the heat treatment process.

[0221] After the material cooled to room temperature, it was ground using a ball mill for 2 hours. After that, it was heated to 750°C at a rate of 10°C per hour under nitrogen protection and kept at that temperature for 12 hours to further improve the structure of the material.

[0222] After the above heat treatment and grinding steps, the obtained material is thoroughly washed with distilled water to remove possible impurities, and then dried to finally obtain the negative electrode graphite material. Finally, this material is used to prepare the soft pack battery.

[0223] The negative electrode material in the above-mentioned embodiments 1 to 3 is a negative electrode graphite material with a supported Pt / Fe2O3 catalyst, and the negative electrode material in the comparative example 1 is a common graphite material.

[0224] Each of the above four examples corresponds to a battery. The same positive electrode material can be used to compare the above four examples to obtain Table 1 and Table 2:

[0225]

[0226] Table 1 is a comparison table of the main gas products of battery thermal runaway

[0227] The first column on the left side of Table 1 is a description of the detection object. 2-Butene is an unsaturated hydrocarbon and a type of olefin. Dimethyl ether is a simpler ether compound, commonly used in solvents and fuels. Benzene is an aromatic hydrocarbon, widely present in petroleum products. Fluorobenzene is a compound formed when one or more hydrogen atoms in the benzene molecule are replaced by fluorine atoms. EMC refers to methyl acetate (Methyl ethyl ketone, MEK), a commonly used organic solvent. "The time t1 when CO is first detected" and "the total concentration of CO detected Cco,totle" are two parameters related to the detection of carbon monoxide (CO), which refer to the time point when carbon monoxide is first detected and the total concentration of carbon monoxide detected during this period, respectively.

[0228] The second column on the left is the test unit or reference description, where ppm refers to percentage, which can be one part per million. Columns 3 to 6 list the parameters corresponding to different examples.

[0229] According to the data analysis in Table 1, it can be clearly seen that when the battery using the composite negative electrode material C@Pt / Fe2O3 is used, the amount of CO and other organic products generated during thermal runaway is significantly reduced. In addition, the use of this composite catalyst also effectively delays the time when the peak concentration of these harmful gases appears. This means that the composite catalyst on the surface of the negative electrode can consume these harmful organic gases, thereby avoiding the leakage of harmful gases in the case of thermal runaway, which greatly improves the safety performance of lithium batteries.

[0230] Time for voltage to reach 4.8V / s Maximum temperature of battery surface / ℃ Embodiment 1 525 32.9 Embodiment 2 485 33.6 Embodiment 3 304 24.9 Comparative Example 1 469 37.1

[0231] Table 2 is the battery overcharge test data

[0232] From Table 2 and Figures 5 to 8 From the data, it can be observed that when the soft-pack batteries of Examples 1 to 3 are subjected to a small current overcharge test, they can all quickly reach a voltage threshold of 4.8V, thereby triggering an overcharge protection mechanism. At the same time, the temperature detected at various parts of the battery is maintained below 35°C, which indicates that the negative electrode of the composite catalyst can effectively convert combustible organic gases, reduce heat generation, and thus significantly improve the safety performance of the battery. In contrast, although the soft-pack battery of the comparative example can also reach 4.8V and trigger overcharge protection in a small current overcharge test, the temperature of the large area and back of the battery exceeds 35°C. This phenomenon shows that in the case of overcharge out of control, the battery generates a large amount of heat, leading to material damage.

[0233] exist Figures 5 to 8 The data has two X-axes on the left and right and a Y-axis at the bottom. The X-axis on the left is temperature data in degrees Celsius; the X-axis on the right is voltage data in volts. The Y-axis is time data in seconds. The curves in the table take the peak value as an example. From top to bottom, they are the voltage change curve, the large surface temperature change curve, the back surface temperature change curve, the positive electrode temperature change curve, the negative electrode temperature change curve, and the ambient temperature change curve (maintained unchanged).

[0234] The voltage variation curve corresponds to the reference of the X-axis on the right and the Y-axis at the bottom, that is, the curve expresses the relationship curve of voltage variation over time.

[0235] For other curves except the voltage change curve, the corresponding reference is the X-axis on the left and the Y-axis at the bottom, that is to say, the curve expresses the relationship curve of temperature change over time. Among them, the large surface temperature change curve and the back surface temperature change curve in Examples 1 to 3 are almost overlapped, and the large surface temperature change curve and the back surface temperature change curve in the comparative example do not overlap at the peak position, and the peak value of the large surface temperature change curve is slightly lower than the peak value of the back surface temperature change curve. The ambient temperature is controllable and can be used as a quantitative method.

[0236] The battery of the present application may be an LFP (Lithium Iron Phosphate, LFP for short) soft-pack battery or other types of batteries. Taking the LFP soft-pack battery as an example, the LFP soft-pack battery refers to a soft-pack lithium battery that uses lithium iron phosphate as the positive electrode material. Thermal runaway refers to the phenomenon that under certain circumstances, the temperature of the battery rises to a certain level, causing the chemical reaction inside the battery to get out of control, generating a large amount of heat and gas, which may cause the battery to overheat, burn or even explode.

[0237] The main gas products of LFP soft-pack battery thermal runaway usually include but are not limited to the following: 1. Hydrogen (H2) 2. Carbon monoxide (CO) 3. Carbon dioxide (CO2) 4. Hydrogen fluoride (HF) 5. Oxygen (O2) 6. Nitrogen (N2), etc. These gases are generated due to the decomposition reaction of the electrolyte and electrode materials inside the battery at high temperatures. Understanding these gas products is helpful for battery safety design and thermal management, which can help predict and prevent thermal runaway events.

[0238] The positive electrode material of the present application can be lithium iron phosphate (chemical formula LiFePO4, usually referred to as LFP), or other types of positive electrode materials. The ratio of the positive electrode system can be LFP: PVDF: SP = (94-96): (3.5-4.5): (0.5-1.5). Such a ratio ensures the stability of the positive electrode material and the performance of the battery. Among them, PVDF is polyvinylidene fluoride (Polyvinylidene Fluoride), a commonly used binder used in battery electrode materials to help the electrode material maintain structural stability. SP is a conductive additive, which is added to the battery electrode to increase the conductivity of the electrode, thereby improving the charge and discharge performance of the battery.

[0239] The negative electrode system has a ratio of graphite: CMC: SBR = 96:2:2, which helps to improve the cycle stability and conductivity of the battery. In terms of electrolyte, 1M LiPF6 is used as the solute, and the solvent is a mixture of ethyl carbonate (EC) and diethyl carbonate (DEC). Among them, CMC is carboxymethyl cellulose (Carboxymethyl Cellulose), a derivative of natural cellulose, used as a binder for the negative electrode of the battery.

[0240] In a second aspect, the present application provides a battery, wherein the negative electrode material in the battery is made using the method for preparing the negative electrode material for preventing overcharge thermal runaway as described above.

[0241] The negative electrode material made by the above-mentioned method for preparing the negative electrode material to prevent overcharge and thermal runaway can reduce costs and improve the safety of the battery. Specifically, the present application improves the negative electrode material in a low-cost and green way and uses asphalt to turn waste into treasure, and prepares a Pt / Fe2O3-loaded catalyst composite negative electrode material, that is, solid phase sintering-mechanical grinding-solid phase sintering is adopted to finally prepare a battery to prevent overcharge and thermal runaway. The lithium iron phosphate battery with Pt / Fe2O3-loaded catalyst prolonged the time for the CO concentration to reach the peak in the thermal runaway test, effectively preventing the occurrence of thermal runaway, while avoiding the large-scale generation of other toxic gases. Temperature detection proves that this method can effectively reduce the heat generation of the battery in thermal runaway, avoid the damage of the material crystals caused by overcharging of the battery, and help to improve the safety of the lithium iron phosphate battery.

[0242] In a third aspect, the present application provides an electrical device, which uses the above-mentioned battery. The electrical device includes a device body, and the battery is installed in the device body.

[0243] After the battery with the above-mentioned anti-overcharge thermal runaway negative electrode material is applied to electrical equipment, it can reduce costs and improve the safety of the equipment. Specifically, the present application improves the negative electrode material in a low-cost and green way and uses asphalt to turn waste into treasure, and prepares a Pt / Fe2O3 supported catalyst composite negative electrode material, that is, solid phase sintering-mechanical grinding-solid phase sintering is adopted to finally prepare a battery that prevents overcharge thermal runaway. In the thermal runaway test, the lithium iron phosphate battery with Pt / Fe2O3 supported catalyst prolonged the time for the CO concentration to reach the peak, effectively preventing the occurrence of thermal runaway, and avoiding the large-scale generation of other toxic gases. Temperature detection proves that this method can effectively reduce the heat generation of the battery in thermal runaway, avoid the damage of the material crystals caused by overcharging of the battery, and help to improve the safety of the lithium iron phosphate battery.

[0244] The same or similar numbers in the drawings of this application correspond to the same or similar parts; in the description of this application, it should be understood that if the terms "upper", "lower", "left", "right", etc. indicate the orientation or position relationship, they are based on the orientation or position relationship shown in the drawings. This is only for the convenience of describing this application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as a limitation on this patent. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.

[0245] The above are only preferred examples of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a negative electrode material for preventing overcharge thermal runaway, characterized in that: The preparation method comprises: Mechanically stirring the emulsified asphalt in distilled water according to a preset solid-liquid ratio to obtain a first solution; Adding ammonia chloroplatinum, ammonium ferric citrate and sodium chloride in a preset mass ratio into the first solution to obtain a second solution; heating the second solution and stirring it, so that the solutes in the second solution react with each other and obtain a third solution; freeze-drying the third solution to obtain a first solid composition; Heating the first solid composition to a first preset temperature in a heating chamber and keeping the temperature constant to obtain a second solid composition; cooling the second solid composition to room temperature and grinding; heating the ground second solid composition to a second preset temperature in the heating chamber and keeping the temperature constant to obtain a third solid composition; Washing the third solid composition with distilled water and drying it to obtain an overcharge thermal runaway prevention negative electrode material; Wherein, the heating chamber is filled with protective gas, and the negative electrode material for preventing overcharging and thermal runaway is a negative electrode graphite material with a loaded Pt / Fe2O3 catalyst.

2. The method for preparing the overcharge-proof thermal runaway negative electrode material according to claim 1, characterized in that: The preset solid-liquid ratio of the emulsified asphalt is 1 g / mL:20 g / mL, and the emulsified asphalt is mechanically stirred in distilled water for 0.25 h-1 h to obtain the first solution.

3. The method for preparing the overcharge-proof thermal runaway negative electrode material according to claim 1, characterized in that: In the step of adding ammonia chloroplatinum, ammonium ferric citrate and sodium chloride in a preset mass ratio into the first solution to obtain a second solution: The preset mass ratio of the ammonia chloroplatinum, the ammonium ferric citrate, the sodium chloride and the emulsified asphalt is: 1:5:5:89; Alternatively, the preset mass ratio of the ammonia platinum, the ammonium ferric citrate, the sodium chloride and the emulsified asphalt is: 1:3:7:

89.

4. The method for preparing the overcharge-proof thermal runaway negative electrode material according to claim 1, characterized in that: The step of heating the second solution and stirring, wherein the solutes in the second solution react with each other to obtain the third solution comprises: heating the second solution to 40°C-100°C; The second solution being heated is stirred for 2 h to 10 h to obtain the third solution.

5. The method for preparing the overcharge-proof thermal runaway negative electrode material according to claim 4, characterized in that: The second solution was heated to 45° C. and stirred for 10 hours during the heating process, and then freeze-dried for 12 hours to obtain the first solid composition; Alternatively, the second solution is heated to 50° C. and stirred for 12 hours during the heating process, and then freeze-dried for 12 hours to obtain the first solid composition; Alternatively, the second solution is heated to 80° C. and stirred for 10 hours during the heating process, and then freeze-dried for 12 hours to obtain the first solid composition.

6. The method for preparing the overcharge-proof thermal runaway negative electrode material according to claim 1, characterized in that: The step of heating the first solid composition to a first preset temperature in a heating chamber and keeping the temperature constant to obtain a second solid composition comprises: Filling the heating chamber with the protective gas; placing the first solid composition in the heating chamber; Raise the temperature to 400°C-550°C at a heating rate of 5°C-15°C; The mixture is kept warm for 10 h to 24 h to obtain the second solid composition.

7. The method for preparing the overcharge-proof thermal runaway negative electrode material according to claim 1, characterized in that: The step of heating the ground second solid composition to a second preset temperature in the heating chamber and keeping the temperature to obtain a third solid composition comprises: Filling the heating chamber with the protective gas; placing the second solid composition in the heating chamber; Raise the temperature to 550°C-800°C at a heating rate of 5°C-15°C; The mixture is kept warm for 5 h to 24 h to obtain the third solid composition.

8. The method for preparing the overcharge-proof thermal runaway negative electrode material according to claim 7, characterized in that: The heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 750° C. at a heating rate of 5° C., and the temperature is kept for 12 hours to obtain the third solid composition; Alternatively, the heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 650° C. at a heating rate of 10° C., and the temperature is kept for 12 hours to obtain the third solid composition; Alternatively, the heating chamber is filled with nitrogen, the second solid composition is placed in the heating chamber, the temperature is increased to 800° C. at a heating rate of 10° C., and the temperature is kept for 24 hours to obtain the third solid composition.

9. A battery, characterized in that: The negative electrode material in the battery is made by the method for preparing the overcharge thermal runaway-proof negative electrode material according to any one of claims 1 to 8.

10. An electrical device, characterized in that: include: A battery as claimed in claim 9; and, The device body is provided with the battery installed in the device body.